The Effects of an Individual and Family Self-Management Program for Slowing Disease Progression via a Mobile Application on Self-Management Behaviors and Clinical Outcomes in Patients with Stage 3 Chronic Kidney Disease in Thailand: A Quasi-Experimental Study - Suphitsara Kulsuwan; Chutima Chantamit-O-Pas; Panicha Ponpinij; Pattanapong Chantamit-O-Pas (Korean Journal of Adult Nursing, 2026)
Purpose: Stage 3 chronic kidney disease (CKD) is highly prevalent and often progresses to end-stage renal disease without effective self-management. This study examined the effects of an Individual and Family Self-Management Program delivered via a mobile communication application on self-management behaviors and clinical outcomes among patients with stage 3 CKD.Methods: A 12-week quasi-experimental study with a pretest-posttest control group design was conducted among 50 patients with stage 3 CKD at a tertiary hospital in Thailand, between January and May 2024. The intervention group received a self-management program grounded in Individual and Family Self-Management Theory and delivered via the LINE chatbot. The program included educational content, self-regulation strategies, and structured family support, while the control group received usual care. Outcomes included self-management behaviors, estimated glomerular filtration rate (eGFR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and hemoglobin A1c (HbA1c). Analysis of covariance was used to adjust for baseline differences.Results: After adjustment for baseline values, the intervention group showed significantly greater improvements in self-management behaviors (F=7.92, p<.05) and eGFR (F=52.92, p<.001) compared with the control group. Significant reductions were also observed in SBP (F=26.84, p<.001), DBP (F=12.61, p<.05), and HbA1c levels (F=7.74, p<.05).Conclusion: A mobile-based Individual and Family Self-Management Program effectively improved self-management behaviors and key clinical outcomes among patients with stage 3 CKD, supporting the integration of family engagement and digital technology in chronic disease care.
Keywords: Dialysis and Renal Disease Management; Mobile Health and mHealth Applications; Diabetes Management and Education